Global citizenship in the teaching practice of the instructor of the SED-Cisco academies. - Rojas Pacheco, Adolfo Eleazar
Global citizenship has gained interest among academics and educators, especially since its inclusion in the 2030 Agenda for Sustainable Development. This article is framed within the framework of pedagogical research. It aims to analyze the teaching practice of the SED-Cisco instructor. It was approached from the phenomenological paradigm. The information was obtained through a survey, which was subjected to a content analysis. The instrument revealed that the practice of the SED-Cisco instructor teacher is developed in four axes: Strategies, innovative curriculum, 21st century competencies and digital citizenship. It is concluded that the SED-Cisco teacher educator is a techno-pedagogue who appropriates technology for the construction of knowledge. These practices respond to the demands of the local and global labor market based on global citizenship. The curricular promotion of global citizenship presents tensions with the problem-based methodology, since the former evokes global thinking and the latter faces local context situations.